Mesothelioma and thymic tumors: Treatment challenges in (outside) a network setting. Issue 1 (January 2019) - ,; Hackl, Monika; Eycken, Elizabeth Van; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: The management of patients with mesothelioma and thymic malignancy requires continuous multidisciplinary expertise at any step of the disease. A dramatic improvement in our knowledge has occurred in the last few years, through the development of databases, translational research programs, and clinical trials. Access to innovative strategies represents a major challenge, as there is a lack of funding for clinical research in rare cancers and their rarity precludes the design of robust clinical trials that could lead to specific approval of drugs. In this context, patient-centered initiatives, such as the establishment of dedicated networks, are warranted. International societies, such as IMIG (International Mesothelioma Interest Group) and ITMIG (International Thymic Malignancy Interest Group) provide infrastructure for global collaboration, and there are many advantages to having strong regional groups working on the same issues. There may be regional differences in risk factors, susceptibility, management and outcomes. The ability to address questions both regionally as well as globally is ideal to develop a full understanding of mesothelioma and thymic malignancies. In Europe, through the integration of national networks with EURACAN, the collaboration with academic societies and international groups, the development of networks in thoracic oncology provides multiplex integration of clinical care and research, ultimately ensuring equal access to high quality care to all patients, with the opportunity of conducting high level clinical and translational research projects.